Whole Blood Mycobacterial Growth Assays for Assessing Human Tuberculosis Susceptibility: A Systematic Review and Meta-Analysis - Bok, Jeroen (2021)
Funding is gratefully acknowledged from: the Wellcome Trust (awards 057434/Z/99/Z, 070005/Z/02/Z, 078340/Z/05/Z, 105788/Z/14/Z, and 201251/Z/16/Z); UK-AID DFID-CSCF; the Joint Global Health Trials Scheme (award MR/K007467/1) with funding from the UK Foreign, Commonwealth and Development Office, the UK Medical Research Council, the UK Department of Health and Social Care through the National Institute of Health Research (NIHR) and Wellcome; the STOP TB partnership's TB REACH initiative funded by the Government of Canada and the Bill & Melinda Gates Foundation (awards W5_PER_CDT1_PRISMA and OPP1118545); CONCYTEC/FONDECYT award code E067-2020-02-01 number 083-2020; and the charity IFHAD: Innovation For Health And Development.